Sustainability Goals - Can we Reduce Malnutrition? - Fróna, Dániel (International Journal of Engineering and Management Sciences, 2020)
Nowadays, some parts of the world hunger still exists. One of the milestones of the Millennium Development Goals (MDGs) is eradicating hunger. These goals include a road map for progress and documenting specific steps to combat hunger. Another type of hunger that has been very common in these days is hidden hunger. Eradicating extreme poverty and hunger is still an illusion. The number of people living in extreme poverty and malnutrition has fallen slightly in recent years. Measuring hunger is a very complex issue. The Global Hunger Index is a tool to comprehensively measure and monitor hunger at global, regional and national levels. Despite noticeable improvements, the question remains: will the world achieve its Sustainable Development Goals (SDGs), including the eradication of hunger, by 2030? Despite these efforts, even in economically developed countries, hunger or food insecurity still exist.